Posted:

**Oct 27, 2018 1:12 pm**...........ln (x/m – as)

y = __________________

........... r2

r2y = ln (x/m -as)

erry = x/m – as

merry = x-mas

y = __________________

........... r2

r2y = ln (x/m -as)

erry = x/m – as

merry = x-mas

Lifeboat for the rational mind :D

http://www.rationalskepticism.org/

http://www.rationalskepticism.org/viewtopic.php?p=2659474#p2659474

Posted: **Oct 27, 2018 1:12 pm**

...........ln (x/m – as)

y = __________________

........... r2

r2y = ln (x/m -as)

erry = x/m – as

merry = x-mas

y = __________________

........... r2

r2y = ln (x/m -as)

erry = x/m – as

merry = x-mas